PENEGAKAN HUKUM TERHADAP PELAKU PENGGADAIAN MOBIL SEBAGAI OBJEK JAMINAN FIDUSIA DI WILAYAH HUKUM POLRESTA PEKANBARU - Zainal Abidin; Zulfikar Jaya Kusuma; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Car Mortgage as an Object of Fiduciary Guarantee is a fight that occurs in the community, because the increasing needs of the community are not comparable to the economic need to buy contingents related to goods, such as cars. How do you raise questions about how to create existing fiction? Mortgage car as an object of fiduciary security in the background by economic factors or personal needs that are not fulfilled so as to make the deviant relationship. Car pawning events as objects Fiduciary collateral does not happen a little to get a big profit and harm many others. However, until now the law enforcement of the sentence of car lifts as an object of fiduciary guarantee each year shows an increase in numbers. This type of research is sociological legal research, because in this study the author immediately conducts research at a location or place that is researched to provide complete bases and explains about the Pekanbaru City Police, as well as research and research related to research related to the problems discussed in the research this, the data sources used, primary data, secondary data and tertiary data, data collection techniques, in this study with interviews and literature studies. From the results of the research problem two main things that can be concluded. first, law enforcement on the protection of car pawning as an object of fiduciary collateral in the jurisdiction of Pekanbaru Police. The two challenges encountered in law enforcement against the pawning of cars as objects of fiduciary collateral by the Pekanbaru City Police Resort are various internal factors and external factors. Advice from the author, first, Seharausnya, law enforcement, law enforcement, prevention, participation Increased intensity by making a special team in following up that is not corporative. the police must be more active in terms of law enforcement, not only asking the creditors to enforce the law. The authorities should ask for greater coverage to reveal who gave the false identities contained in the report. The responsible party can reveal its identity can be revealed and cannot be released by inhaling fresh ingredients.Keywords: Law Enforcement-Against Carriers as Carriers of Fiduciary Assurance